COMBINATION OF SHOTS NUMBER MAINTENANCE AND STEM BENDING TECHNIQUES ON THE GROWTH AND YIELD OF TOMATO PLANTS (Solanum lycopersicum) - Muhammad Jaelani; Ferdianto Samudra; Lisa Navitasari (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to determine the effect of a combination of shoot number maintenance and stem bending techniques on the growth and production of tomato plants ( Solanum lycopersicum ) variety Servo F1, analyze the feasibility of farming, and design the dissemination of research results to farmers. The study used a factorial randomized block design (RAK) with two factors: shoot number maintenance (all shoots, 1 shoot , 2 shoots, and 3 shoots) and stem bending techniques (without bending and bent). Data were analyzed using ANOVA at the 5% level and continued with Duncan's test. The results showed that the treatment of shoot number maintenance significantly affected plant height only at 63 days after planting, with the treatment without shoot restriction producing the tallest plants (129.17 cm). Stem bending treatment did not significantly affect plant height or number of leaves, but significantly affected fruit weight and number of fruits. There was a significant interaction between shoot maintenance and stem bending. to heavy fruit (total harvest ) and number fruit . The A1B0 combination (1 shoot, without layering) produced the highest total fruit weight (1.1950 kg/planting season). Financial feasibility analysis at a scale of 1,000 m² showed that all treatments were feasible with an R/C Ratio > 1, and A1B0 provided the highest efficiency (R/C = 3.53; net profit Rp26,994,500). Dissemination to 20 farmers through video media proved effective with an average N-Gain of 0.51 (Medium category).